Determination of Health Literacy Levels of Senior Nursing Students' Parents of a University - Ufuk Kaya; Dilay Necipoğlu; Nazlı Turgut; Hatice Bebiş (Galenos Publishing House, 2022)
Objective:This study aimed to determine the health literacy levels of nursing senior students' parents and the factors affecting these levels.Methods:The universe of this study, which was performed in a cross-sectional and descriptive type, was the parents of the senior students of the nursing department of a private university (n = 156). The data were collected with Turkey Health Literacy Scale-32 by students who made face to face interviews with their parents. The data of the research were collected from April to May 2019.Results:Scale's total scores of the parents were determined to be 29.90 ± 3.93. A statistically significant difference was found between the parents' scale scores and average age, income-expenditure status, and educational status (p < .05).Conclusion:According to the scale's total score, parents are at the level of "problem-limited" health literacy. For this, level determinations should be made, consultancy services should be provided, awareness raising training should be provided, public should be encouraged, and such research should be done more.